Aktuelle Entwicklungen und Trends in den Regionen Mittelost-/Südosteuropas und des Donauraums; Current developments and trends in the regions of Central, East and Southeast Europe and the Danube region - Helmut Hiess; Roman Römisch (The Vienna Institute for International Economic Studies (wiiw), 2017)
Die Studie analysiert aktuelle Entwicklungen und Trends in den Ländern Zentral- und Osteuropas sowie Süd- und Südosteuropas und deren Implikationen für die österreichische Regionalpolitik. Das Ziel der Studie ist, einen Beitrag zur Evaluierung der gegenwärtigen Regionalpolitik innerhalb Österreichs wie auch der EU zu leisten. Dafür untersucht die Studie überblicksmäßig folgende Punkte a) aktuelle wirtschaftliche Trends in Österreich und den Ländern des Donauraums (inklusive Polen), b) die Verknüpfung Österreichs mit diesen Ländern hinsichtlich Außenhandel, Investitionen, Arbeitsmärkte, Transport und Tourismus und c) die österreichische Regionalpolitik im nationalen sowie im europäischen Kontext. Auf Basis der Analyseergebnisse ergeben sich Rückschlüsse und Empfehlungen für die Entwicklung von Politikinitiativen in Österreich und der EU. – – The study analyses recent trends and developments in the Central and East European (CEE) and Southeast European (SEE) countries and the implication for Austrian regional policy. The aim of the study is to contribute to the evaluation of current Austrian and European regional policy instruments as well as to the Austrian preparation of the post-2020 EU Cohesion policy. In an overview, the study analyses a) the main (economic) trends in Austria and the CEE/SEE countries; b) their trade, investment, labour market, transport and tourism relationships; and c) Austrian regional policy in the national and European context. The results of the analysis allow drawing conclusions and recommendations for developing policy initiatives in Austria and the EU.
Keywords: E00; E24; F14; F15; F21; J20; J30; O11; R58; 330; Österreich; Europäische Union; Regionalpolitik; Donauraum; Zentral- und Osteuropa; Süd- und Südosteuropa; Austria; European Union; regional policy; Danube region; Central and Eastern Europe; Southehiesast Europe